Quality Management Practices and Performance of Public Secondary School Heads in Pangasinan, Philippines - Jeger, editor (Future Science / FSH-PH Publications, 2020)
This is a descriptive study which determined and analyzed the quality management practices of public secondary school heads. The study included the school heads and teachers in all Schools Division in Pan-gasinan. The identified quality management practices are based on the parameters of APPES Manual. Kendall’s tau correlation coefficient was utilized to identify the significant relationship in the quality man-agement practices of public secondary school heads to the perfor-mance of their respective schools. The researcher used questionnaire, interview and google form to gather the needed data. Same set of questionnaire was utilized for the teachers and school heads as re-spondents of this study. Findings of the study revealed that stake-holders were truly a great agent in improving the public secondary schools. Therefore, school heads must be eager to do this to have a strong partnership and participation of the stakeholders in the school. They contribute a lot for the direction leading to greater learn-ing outcomes. Also, it was found out that weak correlation was hardly related to the quality management practices of the school heads with regard to the performance of their respective schools. Further, a pro-posed plan of action with regard to the indicators that were found out moderate would be presented to public secondary schools for them to better identify the risk and opportunities so to attain and maintain quality management practices of school heads and school perfo-mance in the Department of Education.